The problem of givenness in Patočka’s thought - Barcaro, Marco (Investigaciones Fenomenológicas, 2021)
This paper presents how the philosophical key concept of givenness is reinter-preted in Patočka's reflection. Starting from the Husserlian idea, according to which things are given in the pure immanence of consciousness, Patočka criticized this "subjectivist" orientation because it doesn’t adequately develop the appearing in the phenomenal field. The second section analyzes three main methodical shifts concerning: the nature and the role of the subject, its relationship with the transcendence, the self-giving of the world as a whole. The third section compares Patočka's reflection and two cross-references to similar undertaking in the history of phenomenology. The theme of givenness brings us back in the end to the biggest problem within which philosophy has always worked: world manifestation. Patočka tried to clarify this issue through two metaphors (the mirror and the painting), but he also highlighted as it concerns the way in which man interprets his existence. Esta contribución presenta como el concepto filosófico de “donación” es reinterpretado en la reflexión de Patočka. Partiendo de la lección husserliana, gracias a la cual las cosas son dadas en la pura inmanencia de la consciencia, él critica esta orientación “subjetivista” porque no desarrolla adecuadamente el tema del aparecer en el campo fenomenal. La segunda sección analiza tres desplazamientos metódicos que abarcan: el rol del sujeto, su relación con la trascendencia, el darse a sí mismo del mundo en su totalidad. La tercera sección compara la reflexión de Patočka con dos referencias cruzadas a algunos intentos similares en la historia de la fenomenología. El tema de “la donación”, por tanto, nos traslada al mayor problema con el que ha trabajado siempre la filosofía: la manifestación del mundo. Patočka intentó esclarecer este problema mediante dos metáforas (el espejo y la pintura), pero también subrayó cómo concierne el modo en el que el hombreinterpreta la propia existencia.